2021
DOI: 10.1177/0361198121991833
|View full text |Cite
|
Sign up to set email alerts
|

Sidewalk Static Obstructions and Their Impact on Clear Width

Abstract: Data on sidewalks have long been deficient. But advances in remote sensing are beginning to increase data prevalence and accuracy. These sidewalk datasets rarely, if ever, account for static obstructions in the sidewalk such as signs, street furniture, or trees. This paper seeks to determine how much of a difference accounting for static obstructions will make when measuring the clear width of sidewalks. We extracted the minimum width of sidewalk surfaces—both with and without accounting for static obstruction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…A study conducted in Cambridge, MA, for example, evaluated ADA conditions of sidewalks and found that nearly half of all sidewalks within the city did not meet the minimum 36-in. width ADA standard ( 30 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study conducted in Cambridge, MA, for example, evaluated ADA conditions of sidewalks and found that nearly half of all sidewalks within the city did not meet the minimum 36-in. width ADA standard ( 30 ).…”
Section: Literature Reviewmentioning
confidence: 99%